APPLICATION OF MATHEMATICAL SIMULATION TO CHOOSE THE COMPOSITION OF THE THERMAL PROTECTION COATING OF UNDERLAYER - A. M. Amouei; G. R. Mirhosseini; A. Jafari; M. Saadatibaei (Научный вестник МГТУ ГА)
The article considers the use of mathematical modeling while designing thermal protection coating for GTE turbine blades. The results of mathematical simulation are presented and comparison with experimental data is given. The obtained results allow to choose the composition of a underlayer to cover the metal layer of thermal protection coating.